Management of the Guatemalan moth with entomopathogenic nematodes and granulosis virus in “creole apple” potato crops - Mariana Valentina Jaimes Velandia; Ismael Villanueva; Maria del Pilar Márquez Cardona; Adriana Sáenz-Aponte (Egyptian Journal of Biological Pest Control)
Abstract Background Potatoes are a vitally important food crop in Colombia. Both native and commercial varieties are grown, and all are vulnerable to attack by the Tecia solanivora (Povolný 1973) (Lepidoptera: Gelechiidae) which is known as the Guatemalan moth. Nevertheless, some native varieties are more susceptible to damage from this insect. Since this pest appeared in Colombia, management has been mainly chemical. This field study evaluates two entomopathogenic nematodes, Steinernema feltiae SC125, Steinernema carpocapsae BPS, and granulosis virus (Bc), as potential biological management alternatives for controlling the Guatemalan moth in the creole apple (Manzana criolla) potato crop. Results Individual application of granulosis virus and application of this granulosis virus together with infective juveniles (IJs) of S. carpocapsae BPS had better results in terms of percentage reduction of crop damage and improved yields than did application of the combination of granulosis virus and S. feltiae SC125. The use of entomopathogenic nematodes (EPN) and granulosis virus for managing the Guatemalan potato moth is an effective, safe, and sustainable strategy. Conclusions These biological agents can complement each other in their mode of action, effectiveness, and contributions to continuous pest control while minimizing environmental impacts and complying with the principles of integrated pest management.